The Search for a More Effective Distractor in Thought Suppression under Cognitive Load - Wang, Deming (Curtin University, 2017)
The present thesis investigated the role of distractor related variables in thought suppression, including content, perceived satisfaction and immersion. Results suggest that distractors were effective in reducing intrusions and accessibility of the unwanted thought when they were satisfying and immersive, such as when they reflect psychological need satisfaction. A meta-analysis was also conducted to explain heterogeneity in previous thought suppression studies. Findings of the present thesis shed light on thought suppression theories and self-determination theory.